Analisis Geosite Dan Geomorphosite Sebagai Potensi Geowisata Di Daerah Krembangan, Kecamatan. Panjatan, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Ani, Ani Apriani; Aisyah, (ReTII, 2024)
One form of tourism that is becoming increasingly popular in relation to earth sciences is geotourism. Geotourism is a type of sustainable tourism that focuses on the conservation of natural resources. This geoheritage can further develop into a geopark. In addition to exploration, exploitation, and mitigation, earth science also plays a role in revealing geological heritage or earth heritage around us. This research was conducted in Krembangan, an area located in the Panjatan District, Kulon Progo Regency, Special Region of Yogyakarta. This area was chosen due to its rich geological and geomorphological features that are interesting to study. The landscape in Krembangan exhibits a variety of morphological features, including hills, valleys, and rivers. This reflects the processes and events occurring on the earth's surface. The method used in this study is the parameter assessment analysis by Kubalikova (2013), which serves as a modern method for analyzing geotourism potential. The research results indicate that the Krembangan area has geotourism potential in the form of the Goa Kebon waterfall. Based on the feasibility test using qualitative methods, concerning the weight of scientific significance, educational value, economic value, and conservation value, an average total score of 54.5% was obtained, indicating that the Goa Kebon waterfall geotourism can be considered feasible for development as a geotourism site.